ANALISIS FAKTOR YANG MEMENGARUHI KEJADIAN ANEMIA IBU HAMIL DI WILAYAH KERJA PUSKESMAS BIROMARU - Jerniati, Jerniati; Syafar, Muhammad; Azis, Rahmawati; Taurisa, Almaida (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2024)
Anemia is a common problem frequently experienced by pregnant women, where the hemoglobin levels in the blood fall below normal. This condition is often caused by an iron deficiency. This research aims to identify the factors influencing the occurrence of anemia in pregnant women in the work area of Biromaru Health Center, Sigi Regency, Central Sulawesi Province. The research method employed is quantitative with a cross-sectional analytical approach, aiming to observe the relationship between various variables without intervention. The sample consisted of 76 pregnant women. The results indicate a significant relationship between knowledge, attitude, adherence to iron tablet consumption, and nutritional status and the occurrence of anemia in pregnant women in the area. Pregnant women's knowledge about anemia significantly afFects the incidence of anemia. Positive attitudes towards health and adherence to iron tablet consumption also have a significant impact on preventing anemia in pregnant women. In conclusion, the importance of knowledge, positive attitudes towards health, adherence to iron tablet consumption, and attention to nutritional status in preventing anemia in pregnant women is highlighted. Efforts to improve knowledge and awareness among pregnant women, as well as appropriate iron supplementation, can be efFective steps in addressing the issue of anemia in pregnant women in the area.